Police's Role in Investigation Process of Fraud Criminal Act of Civil Servants Candidate (Case Study of Police Station Binjai) - Rizkan Zulyadi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This study tries to discuss the investigation process of civil servants candidate fraud in the jurisdiction of Police Station Binjai, and how are the efforts made by the police in preventing civil servants candidate fraud. The research uses the type of empirical legal research that is a legal research method that functions to see the law in the real sense and examine how the law works in the community. Because in this study examines people in living relationships in the community, empirical legal research methods can be said as sociological legal research. Research conducted based on the study of literature namely books, laws, journals, opinions of legal experts and academics of a scientific nature relating to the problem in writing this thesis. The results obtained are civil servants candidate fraud in the jurisdiction of Police Station Binjai in accordance with procedures, which are carried out by Pro Justitia and Non Pro Justitia with the understanding that there are up to court trials and some only up to the police because between the victims and the suspect made peace and the victim withdrew his complaint so that the police and investigators stopped their investigation on the basis of a North Sumatera Police Chief Telegram letter. Police. : STR / 315 / V / 2011, May 27, 2011 concerning the handling of alternative Dispute Resolution (ADR) cases and also in accordance with the Restotative Justice Principle.